Enhancing writing interest through the STAD model and pakalating media in grade v students - Syafrudin, Imam Maulana; Kironoratri, Lintang; Ristiyani, Ristiyani (Asatiza: Jurnal Pendidikan, 2025)
This study aims to enhance students' interest in writing and participation in learning activities related to direct and indirect sentence materials by utilizing the STAD (Student Teams Achievement Division) model supported by Pakalating media. The research employs a Classroom Action Research (CAR) methodology, conducted over two cycles, with each cycle comprising two sessions. The study was carried out in the fifth-grade class of SDN 2 Mayonglor. Data were collected through interviews, observations, questionnaires, and documentation, and analyzed using a combination of quantitative and qualitative descriptive methods. The findings reveal a significant improvement in students' interest in writing. The questionnaire results indicate that the average percentage of students' interest in writing increased from 35.9% in the first cycle to 81.5% in the second cycle. Similarly, observations of student learning activities show an increase from an average of 68% in the first cycle to 92.2% in the second cycle. These results highlight the effectiveness of the STAD model combined with Pakalating media in fostering enthusiasm, motivating students, and significantly enhancing their interest in writing.